Holy nations and global identities : civil religion, nationalism, and globalisation - Hvithamar, Annika.; Jacobsen, Brian Arly, 1968-; Warburg, Margit. (International Studies in Religion and Society, 2009)
Along with the processes of globalisation and the end of the cold war we have seen an upsurge in religious nationalism and an increasing focus on the role of religion as a legitimising force in democratic secular states. Holy Nations andamp; Global Identities draws on the combined theoretical and historical insight of historians, political scientists and social scientists on the question of nationalism and globalisation with the methodological knowledge of religion presented by sociologists of religion. The book brings genuine theoretical explorations and original case studies on civil religion, nationalism and globalization. It also provides an introduction to the research history of the fields and aims to develop and elaborate on the theories and methodology of the investigated subjects.